The Investigation of Psychological Motives of Creative Abilities in The Omani Musical Intelligence - Alkiyumi, Mohammed Talib (Harmonia: Journal of Arts Research and Education, 2023)
The Sultanate of Oman is characterized by a huge and creative musical heritage that remains mostly preserved. One hundred forty-two different traditional musical genres and styles (funun) have been registered in the Sultanate. This study aimed to investigate the Omanis’ musical creative achievements and the psychological motives behind Omani musical creative achievements. The present qualitative study adopted ethnographic research. The two study’s questions were answered in two stages: firstly, by analysis of relevant documents of Omani genres, and secondly stage based on analysis of documentary films and direct observations. The study showed that the Omanis created such musical achievements, including many genres, rhythms, instruments, and ways of performing. Furthermore, research has shown psychological motives that motivated Omani people to create these various genres, such as provocation of enthusiasm, meditation, religious motivations, poetic competition, and emotional motivation. For each motive, musical genres have been presented.